Common Mental Disorders in Brazilian Graduate Students - Nayara Paula Fernandes Martins Molina; Assis do Carmo Pereira Junior; Gabriela Di Donato; Marina Aleixo Diniz Rezende; Maria Olívia Barboza Zanetti; Vanderlei José Haas; Adriana Inocenti Miasso (Mental Illness)
This study is aimed at ascertaining the prevalence and predictors of common mental disorders (CMD) among Brazilian graduate students (N=5266) during the COVID-19 pandemic. Employing the Self-Reporting Questionnaire (SRQ-20), the study found that CMD prevalence was 63.5%. Variables such as not feeling well psychologically in the past year, the necessity to take leave of absence from activities, residence in different regions, female gender, studying for a master’s degree, extension of deadlines, experience of setbacks in education, COVID-19 risk group membership, self-medication practices, seeking medical assistance, and prior psychological counseling emerged as predictors of CMD. The findings reveal the vulnerability of graduate students to CMDs and risk factors amenable to institutional intervention. To this end, the study provides support for strategies promoting mental health in this population.